Pandemic-related experiences of older adults and people with disabilities - W. Ben Mortenson; Elham Esfandiari; Somayyeh Mohammadi; Brodie Sakakibara; Julia Schmidt; Ethan Simpson; Janice Chan; Holly Reid; Isabelle Rash; Emily Brooks; Gordon Tao; Quinn Krahn; et al. (PLoS ONE, 2025)
The COVID-19 pandemic has had wide reaching effects especially for people with disabilities. Drawing on Sen’s Capability approach, we explored experiences of people with disabilities and older adults using semi-structured interviews that were conducted three to four months after the pandemic was declared. We recruited 71 adults from British Columbia, Canada: adults with spinal cord injuries (n = 22), adults who have experienced a stroke (n = 26), adults with general disabilities (n = 13), and older adults (over the age of 65) without reported disabilities (n = 10). Our analysis identified one overarching theme: “navigating the new normal: the societal reconfiguration of functionings and capabilities” described the challenges and successes participants experienced during pandemic-related restrictions and regulations. This theme encapsulated three sub-themes: 1) “Trying to stay connected: resuming functionings via alternative means,” 2) “Worrying about future capability opportunities,” and 3) “Wanting to exert control in the face of constrained capabilities.” The pandemic created unique challenges for people with disabilities. The capability approach appears to be a helpful lens to interpret pandemic restrictions among people with disabilities, which could inform future policy.